Synthesis and Magnetic Properties of the Ternary Oxofluoride Fe3Sb4O6F6. Issue 39 (12th August 2020) - Ali, Sk Imran; Kremer, Reinhard K.; Skogby, Henrik; Johnsson, Mats
Abstract : The new compound Fe3 Sb4 O6 F6 was prepared by hydrothermal synthesis and its crystal structure was determined from single‐crystal X‐ray diffraction data. The synthesis was made under slightly basic conditions to prevent oxidation of Fe 2+ to Fe 3+ . The compound crystallizes in the cubic space group I ‐43 m with separate crystallographic sites for Fe 2+ and Sb 3+ . Fe3 Sb4 O6 F6 is isostructural with M3 Sb4 O6 F6 (M = Co, Ni, Zn). The crystal structure is comprising distorted [FeO2 F4 ] octahedra connected via corner sharing at F‐atoms and [SbO3 ] trigonal pyramids that form [Sb4 O6 ] units that connect via O‐atoms to the Fe‐atoms. Mössbauer spectroscopy measurements on the hydrothermal synthesis products prove the majority phase contains Fe in the oxidation state +2. Powder X‐ray diffraction suggests that an additional phase of the Mössbauer sample containing Fe 3+ can be attributed to FeSbO2 F2 as secondary phase. Fe3 Sb4 O6 F6 exhibits antiferromagnetic order below ca. 72 K succeeded by a second magnetic phase transition at ca. 30 K. Strong antiferromagnetic spin‐exchange interaction is attributed to 180° Fe–F–Fe superexchange pathways identified in the crystal structure. Abstract : Non‐centrosymmetric Fe3 Sb4 O6 F6 was synthesized by hydrothermal techniques and characterized by X‐ray diffraction data, Mössbauer spectroscopy, and magnetic studies. The compound crystallizes in the cubic space group I ‐43 m with separate crystallographic sites for Fe 2+ and Sb 3+, respectively. Fe3 Sb4 O6 F6 exhibits antiferromagnetic order below ca. 72 K succeeded by a second magnetic phase transition at ca. 30 K.